FORMULATION AND CHARACTERIZATION OF NANOSTRUCTURED LIPID CARRIERS OF TOLBUTAMIDE FOR THE TREATMENT OF TYPE II DIABETES (CAHIERS MAGELLANES-NS, 2024)
This study investigates the formulation and characterization of tolbutamide-loaded nanostructured lipid carriers (NLCs) aimed at enhancing the solubility and bioavailability of this oral hypoglycemic agent. Tolbutamide, commonly used for managing type 2 diabetes, faces challenges related to its low solubility and variable bioavailability. To address these issues, various formulations of NLCs were developed, with a particular focus on formulation F14 due to its favorable properties. Characterization studies revealed that formulation F14 had a particle size of 210.36 nm, which is optimal for enhancing absorption and bioavailability. The entrapment efficiency was determined to be 83.25%, indicating that a significant portion of tolbutamide was successfully encapsulated within the lipid matrix. Furthermore, the drug content was found to be 99.12%, suggesting an effective loading capacity. In vitro drug release studies showed a cumulative release of 90.23% over a 10-hour period, demonstrating a sustained release profile that could lead to prolonged therapeutic effects and improved patient compliance. Kinetic analysis of the release data indicated a zero-order release pattern, meaning that the drug was released at a constant rate over time, which is desirable for maintaining steady drug levels in the bloodstream. Additionally, the zeta potential of formulation F14 was measured at -35.45 mV, suggesting good colloidal stability and minimizing the risk of aggregation. The results indicate that tolbutamide-loaded nanostructured lipid carriers represent a promising drug delivery system, potentially improving the pharmacokinetic profile and therapeutic outcomes for patients managing diabetes. Future research will focus on in vivo evaluations to further validate the effectiveness and safety of this formulation in clinical settings.